2012
DOI: 10.3389/fncom.2012.00089
|View full text |Cite
|
Sign up to set email alerts
|

Seeing via Miniature Eye Movements: A Dynamic Hypothesis for Vision

Abstract: During natural viewing, the eyes are never still. Even during fixation, miniature movements of the eyes move the retinal image across tens of foveal photoreceptors. Most theories of vision implicitly assume that the visual system ignores these movements and somehow overcomes the resulting smearing. However, evidence has accumulated to indicate that fixational eye movements cannot be ignored by the visual system if fine spatial details are to be resolved. We argue that the only way the visual system can achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 186 publications
(322 reference statements)
1
82
0
Order By: Relevance
“…From an 'energy on target' perspective and in light of the small perturbations observed for fixational eye movement [16][17][18], it seems likely that one would wish K to be relatively small (perhaps ≤1). Using (4) and (8), the outermost elements scale the electrical angle phase change by the largest value of (M − 1)/2 so that, based on (22), the total electrical angle phase change at these elements when traversing K null-to-null spatial intervals is…”
Section: Wda Spectral Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…From an 'energy on target' perspective and in light of the small perturbations observed for fixational eye movement [16][17][18], it seems likely that one would wish K to be relatively small (perhaps ≤1). Using (4) and (8), the outermost elements scale the electrical angle phase change by the largest value of (M − 1)/2 so that, based on (22), the total electrical angle phase change at these elements when traversing K null-to-null spatial intervals is…”
Section: Wda Spectral Impactmentioning
confidence: 98%
“…1) via slow movements known as drift and rapid movements known as microsaccades [15][16][17]. While the purpose of these fixational eye movements has long been debated and remains an open research topic, the current consensus is that these small, spatial perturbations improve visual acuity because the associated transients enhance contrast and sensitivity as well as aiding in the resolving of spatial ambiguities.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the emergence of motion streaks appears undesirable for sensation and indeed, mechanisms exist to suppress them. 60,[63][64][65] In contrast, it has been shown that information about motion axes is still present across neuronal activity and can be extracted from motion streaks. [66][67][68][69][70] Thus, motion streaks may be analyzed unconsciously and separately over time [71][72][73][74] to contribute to further analysis such as form-from-motion at higher processing stages.…”
Section: 21mentioning
confidence: 99%
“…The simplest approach, possibly, is to use transient responses -lateral inhibition seems more complex. The method of Ahissar & Arieli (2001, 2012 would be suitable, namely onset times of bursts of "spikes"; here "temporal encoding" is not used, so the outline representation would be the occurrence of the first spike at a particular position.…”
Section: Representations Of Small Objects At the Visual Centrementioning
confidence: 99%
“…A major difference is that geons are invariant with viewpoint, whereas here viewpoint invariance is obtained using attentional planes; a feature of Biederman's theory that is used here is that stored representations are in two dimensions. Ahissar & Arieli (2001, 2012 used spatial coding for coarse, absolute positions, and temporal coding for fine detail using relative positions. That approach for positions is used here, except that relative positions, in the form of traces, are from spatial distributions; traces are used down to a size of area of attention of 20' radius, approximately -they are not suitable for "vernier acuity", i.e.…”
Section: Introductionmentioning
confidence: 99%